Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan Dan Fitur Layanan Terhadap Keputusan Pembelian (Studi Pada Mahasiswa FISIP ULM Di Kota Banjarmasin) - Humaidi Humaidi; Setio Utomo; Dinda Lestari (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
This study aims to examine the Influence of Perceived Usefulnes, Perceived Ease of Use and Service Features on Purchasing Decisions (study on students of FISIP ULM Banjarmasin City who use DANA digital wallets).   The research approach used is a quantitative approach. Samples were taken as many as 96 respondents with purposive sampling technique. Data collection using questionnaires and data analysis using multiple linear regression.   The results of the research proves that Perceived Usefulness have a significant effect partially on Purchasing Decisions with the influence of 0.160 or 16%. Perceived Ease of Use has a significant partial effect on Purchase decisions with the influence of 0.437 or 43.7%. Service Features partially significant effect on Purchase Decisions with the influence of 0.163 or 16.3%. Perceptions of Usefulness, Perceived Ease of Use and Service Features simultaneously have a significant effect on Purchase Decisions with the influence of 0.760 or 76%. Keywords: Perceived Usefulness, Perceived Ease of Use, Service Features, Purchase Decision